Students’ Perception of Instagram Reels as a Medium for Vocabulary Learning - Ivada, Ega Nurdianis; Hapsari, Christianti Tri (Universitas Pahlawan Tuanku Tambusai, 2026)
Learning English vocabulary is a very important foundation because it can strengthen English skills such as reading, writing, listening, and speaking. This study aims to determine how students perceive the use of Instagram Reels as a medium for learning vocabulary and what strategies students often use in learning vocabulary through Instagram Reels. This study uses a qualitative method containing Likert scale questionnaires and interviews with three participants. The data were collected from 15 students of the English Education Study Program. The results shows that students perceive Instagram Reels as interesting and easily accessible. The strategies commonly used are guessing the meaning of words and then translating them using a dictionary or digital translator and they frequently repeat the words and apply them in conversations or sentences. However, students rarely ask others about the meanings of unfamiliar words and plan and evaluate their vocabulary learning process.